Limitação do quantum indenizatório decorrente de dano extrapatrimonial no direito trabalhista após a LEI Nº 13.467/17 - Oliveira, Samuel Libânio Castro de (Universidade Federal Rural do Semi-Árido, 2018)
In the intention of protect the individuals immaterial rights, the Federal Constitution recognizes the great value of immaterial goods, closing the doubts as to their applicability in the labor court. Such an institute is gender, encompassing moral, aesthetic and existential damages. The quantification of damages resulting from damages of this nature was arbitrated according to the magistrate’s understanding of the specific case, that is, according to the severity of the damage and the extent of the damages suffered. Law 13.467/17, known as Labor Reform, brought a series of modifications to the Consolidation of Labor Laws (CLT).Among them, the one that provoked more controversies in the doctrine and jurisprudence is the stipulation of a ceiling of the indemnifying values for off-balance damages, being later revised by Provisional Measure 808/17. The Federal Supreme Court, in declaring the old press law unconstitutional, created jurisprudence in the sense that such a limitation is not possible. In this sense, seeks out to analyze the constitutionality of the legal imposition of a ceiling for convictions for off-balance-sheet damages of work origin. As for the methodological aspect, it is a bibliographical research, based on qualitative data, that will analyze the object of study from the comparative method, evaluating the changes brought by Law 13.467/17.In conclusion, it is understood that the labor reform on this point, even after the revision made by MP 808/17, has a clear defect of unconstitutionality, since it is not for the legislature to create limits to the judiciary's performance in the application of penalties of immaterial goods damages.
Artigo Acadêmico
Keywords: Reforma trabalhista; Dano extrapatrimonial; limitação legal; Constitucionalidade; Labor reform; Non patrimonial damage; Legal limitation; Constitutionality; CIENCIAS SOCIAIS APLICADAS::DIREITO